Brand values in digital marketing What do they mean and how can they affect consumers’ decisions? - Idrisova Husniyya (2021)
Consumption, corporate practices, and marketing initiatives have all been redirected as a result of changing environmental and technical developments. With the advent of the Internet, marketing took on a whole new dimension, resulting in the rise of digital marketing. Because of the value of digitalization and having an online presence, businesses are competing for customers' interest. People are becoming more linked as a result of the digital revolution, making knowledge more available. It has also altered people's purchasing habits. People evaluate the purchasing process and brands now more than ever which makes it harder for businesses. Therefore, having a tight digital marketing strategy is crucial for businesses to be successful for increasing customers loyalty and sales growth. For companies now, not getting an online presence is a bad deal. A business could miss out on a lot of resources that are only available online. Understanding this will assist businesses in appreciating the value of Digital Marketing in a corporate plan. At this paper, researcher aimed to find the digital marketing tools that affect customer decision and how digital marketing helps brands to grow in digital era. Methodology covered qualitative analysis of various brands’ digital marketing strategies and quantitative analysis of the effects of digital marketing tools on customer decision and sales. The researcher chose fashion industry to deeply analyze the effectiveness of digital marketing tools due to the fact that the digital marketing strategies are widely used by apparel industry and it would give better insights into the topic. Therefore, 7 most famous fashion companies were analyzed. The analysis was supported by questionnaire that researcher conducted which aimed to strengthen the results of brands’ analysis. Digital marketing’s effectiveness on gaining strong customer loyalty and growing sales has been proved. The author recommended businesses to use digital marketing tools effectively and efficiently for their businesses to grow faster. It was proved that companies with successful digital marketing strategies have better profitability and were able to grow significant customer loyalty and a brand which owns values for customers.